Recent developments in Ge dots grown on pit-patterned surfaces - Karmous, Alim; Fischer, Inga A.; Kirfel, Olaf; Mattes, Johannes; Oehme, Michael; Werner, Jens; Schulze, Jörg (physica status solidi (b), 2012)
Carrier confinement in Ge dots in a Si matrix has a large influence on electronic and optical properties. These dots, therefore, continue to be of interest for potential device applications. For this, the control over dot geometry, position, composition, and strain is a necessary prerequisite. Ge dots that are deposited on substrates with previously defined nucleation sites, as obtained by a patterning of the substrate, have been at the focus of a number of experimental investigations these last years, precisely because they seem to be suited for incorporation into electronic and optical devices. We review recent results in this research area that are e.g., concerned with analysing the influence of the available patterning and growth parameters on the dots and give an overview of recent developments in device applications. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Germanium; Molecular beam epitaxy; Pit-patterned surface; Quantum dot devices; Quantum dots